2012
DOI: 10.1103/physrevc.86.034909
|View full text |Cite
|
Sign up to set email alerts
|

Rapidity dependence of particle densities inppandAAcollisions

Abstract: We use multiple scattering and energy conservation arguments to describe dn/dη| N A N A as a function of dn/dη| pp in the framework of string percolation. We discuss the pseudorapidity η and beam rapidity Y dependence of particle densities. We present our results for pp, Au-Au, and Pb-Pb collisions at RHIC and LHC.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
39
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 32 publications
3
39
0
1
Order By: Relevance
“…In this scenario of the QGP study, an unexpected feature, namely the "ridge" in the long range near side angular correlation, in distinct class of "high multiplicity" events of proton-proton collisions [10] at √ s = 7 TeV at LHC has triggered revival of an old school of thought [11][12][13][14] of the possibility of formation of a collective medium in pp collisions also. Several of subsequent theoretical and phenomenological studies [15][16][17][18][19][20][21][22][23], in different approaches, endorse the possibility, indicating the need for further investigations in understanding the high-multiplicity pp events vis-a-vis the QGP.In this article, we address the issue of collectivity in high multiplicity pp events in the framework of the String Percolation Model, that has successfully explained the collectivity and the change of phase in nucleus-nucleus collisions [24][25][26]. Also SPM describes the centre-of-mass energy dependence of mid-rapidity multiplicity [25] and the pseudorapidity distributions [26] of produced charged particles in pp collisions, for the entire range of energy, available so far.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…In this scenario of the QGP study, an unexpected feature, namely the "ridge" in the long range near side angular correlation, in distinct class of "high multiplicity" events of proton-proton collisions [10] at √ s = 7 TeV at LHC has triggered revival of an old school of thought [11][12][13][14] of the possibility of formation of a collective medium in pp collisions also. Several of subsequent theoretical and phenomenological studies [15][16][17][18][19][20][21][22][23], in different approaches, endorse the possibility, indicating the need for further investigations in understanding the high-multiplicity pp events vis-a-vis the QGP.In this article, we address the issue of collectivity in high multiplicity pp events in the framework of the String Percolation Model, that has successfully explained the collectivity and the change of phase in nucleus-nucleus collisions [24][25][26]. Also SPM describes the centre-of-mass energy dependence of mid-rapidity multiplicity [25] and the pseudorapidity distributions [26] of produced charged particles in pp collisions, for the entire range of energy, available so far.…”
mentioning
confidence: 99%
“…In this article, we address the issue of collectivity in high multiplicity pp events in the framework of the String Percolation Model, that has successfully explained the collectivity and the change of phase in nucleus-nucleus collisions [24][25][26]. Also SPM describes the centre-of-mass energy dependence of mid-rapidity multiplicity [25] and the pseudorapidity distributions [26] of produced charged particles in pp collisions, for the entire range of energy, available so far.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We had fixed the values of the parameters α 0.34, δ 0.84, k 1 = 1.2 to adjust the equation (7) with pp collisions data [13][14][15], with the same aim as in reference [12], and to extend the description of the pseudorapidity evolution to AA collisions [5]. As a result we have found that we are able to describe the rise with energy in AA and pp collisions with the same power-like exponent and rapidity evolution, due to the energy conservation effects which give rise to an additional energy dependence vanishing at extremely high energies.…”
Section: Epj Web Of Conferencesmentioning
confidence: 99%